Faculty Perceptions of the Competency-Based Dynamic Curriculum (CBDC) for Homoeopathic Medical Education in India: A Pilot Study - Shilpi Rastogi; Ram Jyothis A B (The Bioscan, 2025)
Background: Medical education in India is transitioning to a Competency-Based Education (CBE) framework, with the National Commission for Homoeopathy introducing the Competency-Based Dynamic Curriculum (CBDC) for the Bachelor of Homoeopathic Medicine and Surgery (BHMS) programme. The successful implementation of this new curriculum depends heavily on the preparedness and participation of faculty, yet the transition presents significant challenges. This pilot study was conducted to gather preliminary data on faculty perceptions before a larger investigation. Objectives: To assess faculty perceptions regarding the effectiveness of CBDC in meeting educational goals, identify implementation challenges, gauge stress and workload implications, and collect recommendations for a smoother rollout. Methods: This was a descriptive cross-sectional pilot study. A structured questionnaire with closed-ended and open-ended questions was administered to a purposive sample of 58 faculty members teaching first-year BHMS students. Quantitative data were analysed using descriptive statistics, and qualitative responses were analysed thematically. Results: While over half of the faculty agreed that the CBDC effectively meets educational goals, a significant portion remained neutral on its success in integrating subjects. The implementation was widely perceived as too rapid and a moderate-to-high stressor. Key challenges identified were an acute shortage of faculty, inadequate and inconsistent training, and excessive documentation requirements. There was a strong consensus on the need for comprehensive pre-implementation training, increased staffing, and a phased rollout. Conclusion: Despite general faculty acceptance, the implementation of CBDC faces substantial challenges related to training, workload, and resource allocation. The study highlights the critical need for targeted interventions, such as those recommended by the faculty, to ensure the sustainable success of the curriculum in homoeopathic medical education.